2019
DOI: 10.3390/electronics8070732
|View full text |Cite
|
Sign up to set email alerts
|

A Minimum Mean-Square-Error (MMSE) Decoder for Quasi-Orthogonal Space–Time Block Code

Abstract: The quasi-orthogonal space–time block code (QO-STBC) was introduced to achieve a full transmission rate for the four antennas system. In this paper, a decoding method for the QO-STBC is proposed to improve the bit-error-rate (BER) and to solve a rank-deficient problem. The proposed algorithm is based on the minimum mean-square-error (MMSE) technique. To overcome the implementation problem from the MMSE, an estimation method of the noise variance is developed in this paper. The proposed algorithm is implemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…A Minimum mean square error (MMSE) estimator can be described as "an estimation technique employed in statistics and signal processing that reduces the Mean square error (MSE), a popular indicator of estimator quality, of the fitted values of a dependent variable" [15][16][17][18]. The MMSE estimator`s shape is typically restricted to fall within a particular class of functions since computing the posterior mean is laborious [19].…”
Section: Mmse Algorithmmentioning
confidence: 99%
“…A Minimum mean square error (MMSE) estimator can be described as "an estimation technique employed in statistics and signal processing that reduces the Mean square error (MSE), a popular indicator of estimator quality, of the fitted values of a dependent variable" [15][16][17][18]. The MMSE estimator`s shape is typically restricted to fall within a particular class of functions since computing the posterior mean is laborious [19].…”
Section: Mmse Algorithmmentioning
confidence: 99%
“…The detection matrix used to decode the received signal is 𝐷 4 , 𝐻 𝜐 is the hermitian of 𝐻, and 𝑐 𝑛 is the channel's noise. The detection matrix for QO-STBC in this study can be shown below [18]:…”
Section: The Proposed System Modelmentioning
confidence: 99%